Implementasi Metode Preference Selection Index (PSI) dalam Seleksi Penerimaan Content Creator Media Sosial - Usanto S (Universitas Budi Darma, 2023)
Currently social media in the world of work has an important role and can also be a place of business competition. Social media is now being used as an easier and more efficient promotional platform designed to capture the attention of the audience so as to expand the target market for higher profits. Content creators have an important role for business actors, content creators are responsible for social media owned by business actors. The selection process for accepting content creators is still carried out conventionally so that the selection process is sometimes not appropriate in accepting the best content creators. So with that, business actors must choose quality content creators so that their social media continues to be active and get a wider target audience. In selecting content creators, several criteria have been determined, namely skills, work experience, number of followers, interviews and education. Because of these problems, a system is needed that can assist in obtaining reliable and targeted recommendations. The application of a decision support system in this study was used by implementing the PSI (Preference Selection Index) method in which this method is very helpful in producing the best weight and preference values from alternative data and criteria so that the final result is the recommendation for the best content creator in Medan city in the Alternative A3 is Andriana with a value of 0.9236.